Application of Bluetooth technology in greenhouse environment. monitor and control - LIU Gui-guo; YING Yi-bin (浙江大学学报. 农业与生命科学版)
Based on Bluetooth technology, the collected greenhouse environment data could be transmitted to the control system by way of wireless communication, and thereby it would be much more flexible and conveniently to monitor and control the greenhouse environment. Bluetooth technology, its Ericsson ROK 101007 module, and the features of piconet were introduced, and the method of hardware and software design for the greenhouse environment detecting and controlling system based on Bluetooth technology was presented.